Structural and decorative dialogue between french interiors and fashion design in the 17th and 18th centuries (1643–1750) - Sarah Omran; Bashar Dayoub; Peifeng Yang (Cogent Arts & Humanities)
Interiors and fashion design share key artistic rules and intent focused on shape structure and applied embellishments to creatively articulate the human form. Keeping this in mind, this paper explores the intrinsic connections between clothing and interiors, particularly in the structure and decorative design during France’s Baroque and Rococo periods. By applying the tectonic and scenographic framework, traditionally used in architectural analysis, this study expands these concepts to include fashion design. Through qualitative analysis of literary and historical sources, the research traces a transition from structured tectonic spaces to dynamic scenographic arrangements. The findings uncover a concurrent symmetry in structural and decorative design across these domains, highlighting the intertwined evolution of French interiors and fashion aesthetics in the 17th and 18th centuries.